Turnover and post-bottleneck genetic structure in a recovering population of Peregrine Falcons Falco peregrinus - Ponnikas, Suvi; Ollila, Tuomo; Kvist, Laura (Ibis, 2017)
Dispersal is a process that increases genetic diversity and genetic connectivity of populations. We studied the turnover rate of breeding adults and genetic population structure to estimate dispersal in Peregrine Falcons in Finland. We used relatedness estimates among Finnish Peregrine Falcons over a 5-year period, genotyping over 500 nestlings with 10 microsatellite loci to reveal the rate of turnover. Our results reveal a high turnover rate (21.7%) that does not seem to be correlated with the breeding success of the previous year. The extent of population genetic structure and diversity, and possible signs of the population crash during the 1970s, was assessed with a reduced dataset, excluding relatives. We found genetic diversity to be similar to previously studied falcon populations (expected heterozygosity of 0.581) and no population genetic structuring among our sampled populations. We did not find a genetic imprint of the past population bottleneck that the Finnish Peregrine population experienced. We conclude that high dispersal rates are likely to have contributed to maintaining genetic diversity across the landscape, by mixing individuals within the species' distribution in Finland and thus preventing genetic structuring and negative effects associated with the population decline in the 1970s.